Normative decision theory and reindividuation of the outcomes - Filipović Nenad (Filozofija i Društvo)
This article examines and critiques efforts to preserve the requirements of normative decision theory from counterexamples by reindividuating outcomes. Reindividuation is often employed in response to counterexamples that challenge even the most fundamental requirements of rationality, such as transitivity. These counterexamples demonstrate that even basic rationality requirements can appear to be violated in seemingly rational ways, thus casting doubt on their plausibility. Reindividuation seeks to preserve these requirements by refining the objects of preference in more detailed terms. However, John Broome has pointed out that this strategy can lead to the issue of making the requirements vacuous. We will explore counterexamples to transitivity and demonstrate how reindividuation can lead to this problem of emptiness. Following that, we will review significant attempts to address this problem, showing that they fall short and that any direction we take either makes the requirements too permissive or leaves them unjustified. In the final section, we suggest a less conventional solution: rejecting finer individuation and accepting that the requirements of rationality are not universal. Finally, we point out several established approaches to decision theory that allow for domain-specific requirements.